2019
DOI: 10.1093/infdis/jiz433
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Blunted CD4 T-Cell Responses Underlie Deficient Protective Antibody Responses to Influenza Vaccines in Repeatedly Vaccinated Human Subjects

Abstract: Despite the benefits of yearly influenza vaccination, accumulating evidence suggests that diminished vaccine efficacy may be related to repeated vaccination. Although studied at the level of B-cell responses, CD4 T-cell responses have not yet been examined. In this study, we analyze CD4 T-cell responses to influenza vaccination in subjects who differ in their vaccine history. We find a striking disparity in their responses, with previously vaccinated subjects exhibiting significantly blunted CD4 T-cell respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Consequently, these functional defects impair the humoral response induced by vaccination and the formation of B cell memory (347)(348)(349). It was shown that repeated vaccinations may lead to a reduced CD4 + T cell response, which correlates with a reduced antibody response (350).…”
Section: Influenza Virusmentioning
confidence: 99%
“…Consequently, these functional defects impair the humoral response induced by vaccination and the formation of B cell memory (347)(348)(349). It was shown that repeated vaccinations may lead to a reduced CD4 + T cell response, which correlates with a reduced antibody response (350).…”
Section: Influenza Virusmentioning
confidence: 99%
“…Studies by many groups (reviewed in refs 63,64 ) have shown that individuals who were vaccinated in previous seasons have diminished HA-specific responses to influenza vaccination. We have found that the lower antibody responses in previously vaccinated subjects also exhibit diminished CD4 T-cell responses 65 . Others have shown that preexisting serum antibody levels are also associated with lower subsequent B cell and antibody responses to the influenza vaccines 66,67 .…”
Section: Discussionmentioning
confidence: 76%
“…Although subunit vaccines are generally considered to have limited capacity to boost cellular responses [ 23 ], recent studies have reported the induction of significant HA–specific CD4 T cell responses by Flucelvax [ 7 , 10 ]. While little is still known about the CD8 responses and their protein targets contained in this vaccine, here, we evaluated both CD4 and CD8 responses.…”
Section: Discussionmentioning
confidence: 99%
“…Current vaccines are licensed based on World Health Organization-approved centers that test the vaccine efficacy solely based on standard measures of humoral immunity. Therefore, most studies, including Flucelvax, have focused on evaluating humoral [ 9 ], as well as HA-specific CD4 dependent neutralizing antibody responses [ 10 ]. The antibody responses to any of the viral proteins other than HA are not considered or measured because their role is traditionally dismissed from an immunological and vaccine efficacy perspective.…”
Section: Introductionmentioning
confidence: 99%